2022
DOI: 10.1093/ijnp/pyac074
|View full text |Cite
|
Sign up to set email alerts
|

Default Mode Network Modulation by Psychedelics: A Systematic Review

Abstract: Psychedelics are a unique class of drug which commonly produce vivid hallucinations as well as profound psychological and mystical experiences. A grouping of interconnected brain regions characterised by increased temporal coherence at rest have been termed the ‘Default Mode Network’ (DMN). The DMN has been the focus of numerous studies assessing its role in self-referencing, mind wandering and autobiographical memories. Altered connectivity in the DMN has been associated with a range of neuropsychiatric condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 118 publications
3
43
0
2
Order By: Relevance
“…Consistent evidence was found that psychedelics reduce DMN connectivity, particularly in prefrontal cortex, a crucial node of DMN [5]. This reduction in DMN connectivity is associated with increased connectivity between the DMN and other brain networks, such as the salience and executive control networks, which are involved in emotion regulation and cognitive flexibility [6]. propose that the modulation of the DMN by psychedelics is mediated by the activation of serotonin 2A receptors in the cortex, leading to increased excitability and plasticity of neural networks.…”
Section: Psychedelics Modulate the Default Mode Network(dmn)mentioning
confidence: 64%
“…Consistent evidence was found that psychedelics reduce DMN connectivity, particularly in prefrontal cortex, a crucial node of DMN [5]. This reduction in DMN connectivity is associated with increased connectivity between the DMN and other brain networks, such as the salience and executive control networks, which are involved in emotion regulation and cognitive flexibility [6]. propose that the modulation of the DMN by psychedelics is mediated by the activation of serotonin 2A receptors in the cortex, leading to increased excitability and plasticity of neural networks.…”
Section: Psychedelics Modulate the Default Mode Network(dmn)mentioning
confidence: 64%
“…Additionally, we found that in psilocybin subjects the distribution of idiosyncrasy was systematically shifted, and in particular shifted away from FPN and towards DMN regions. Intriguingly, the DMN is assumed to play a key role in mediating the subjective effects of psilocybin and psychedelics more generally 42 . This assumption is backed by a large body of evidence including the 5-HT2AR expression profile of the DMN 23 and the consistent observation that its activity and connectivity is significantly altered during acute psychedelic states 24,27,43,44 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent resting-state fMRI studies in humans have indirectly assessed the effects of psychedelic agents with brain-wide coverage [14][15][16][17][18][19][20][21][22][23][24][25]. Notwithstanding some preprocessing-dependent inconsistencies [139,141], the consensus is that psilocybin reduces functional connectivity within association networks, particularly within the default mode network [14,[23][24][25]142]. This effect has been hypothesized to reflect the subjective experience of ego dissolution [11,16,27,29].…”
Section: 22) Effects Of Psychedelic Agents On Resting-state Fmri In H...mentioning
confidence: 99%